Host competence of African rodents Arvicanthis neumanni, A. niloticus and Mastomys natalensis for Leishmania major - Sadlova, Jovana; Vojtkova, Barbora; Hrncirova, Katerina; Lestinova, Tereza; Spitzova, Tatiana; Becvar, Tomas; Votypka, Jan; Bates, Paul; Volf, Petr (International journal for parasitology. Parasites and wildlife, 2019)
Cutaneous leishmaniasis caused by Leishmania major is a typical zoonosis circulating in rodents. In Sub-Saharan Africa the reservoirs remain to be identified, although L. major has been detected in several rodent species including members of the genera Arvicanthis and Mastomys. However, differentiation of true reservoir hosts from incidental hosts requires in-depth studies both in the field and in the laboratory, with the best method for testing the infectiousness of hosts to biting vectors being xenodiagnosis. Here we studied experimental infections of three L. major strains in Arvicanthis neumanni, A. niloticus and Mastomys natalensis; the infections were initiated either with sand fly-derived or with culture-derived Leishmania promastigotes. Inoculated rodents were monitored for several months and tested by xenodiagnoses for their infectiousness to Phlebotomus duboscqi, the natural vector of L. major in Sub-Saharan Africa. The distribution and load of parasites were determined post mortem using qPCR from the blood, skin and viscera samples. The attractiveness of Arvicanthis and Mastomys to P. duboscqi was tested by pair-wise comparisons. Three L. major strains used significantly differed in infectivity: the Middle Eastern strain infected a low proportion of rodents, while two Sub-Saharan isolates (LV109, LV110) infected a high percentage of animals and LV110 also produced higher parasite loads in all host species. All three rodent species maintained parasites of the LV109 strain for 20-25 weeks and were able to infect P. duboscqi without apparent health complications: infected animals showed only temporary swellings or changes of pigmentation at the site of inoculation. However, the higher infection rates, more generalized distribution of parasites and longer infectiousness period to sand flies in M. natalensis suggest that this species plays the more important reservoir role in the life cycle of L. major in Sub-Saharan Africa. Arvicanthis species may serve as potential reservoirs in seasons/periods of low abundance of Mastomys.
Keywords: Grass rats; Arvicanthis; Leishmaniases; Multimammate mice; Wild reservoir; Xenodiagnosis; Mastomys